Safety and efficacy of functional laryngectomy for end‐stage dysphagia. (17th July 2017) - Topf, Michael C.; Magaña, Linda C.; Salmon, Kelly; Hamilton, James; Keane, William M.; Luginbuhl, Adam; Curry, Joseph M.; Cognetti, David M.; Boon, Maurits; Spiegel, Joseph R.
Abstract : Objectives/Hypothesis: To evaluate functional outcomes and complication rate after total laryngectomy (TL) for dysfunctional larynx with end‐stage dysphagia. Study Design: Retrospective chart review. Methods: Chart review was performed on all patients who underwent TL from January 2008 to July 2016 at a single tertiary academic medical center. Patients who underwent TL for dysfunctional larynx without preoperative evidence of malignancy were included. Main outcome measures were post‐TL functional swallowing and speech outcomes, and complication rate. Results: The study included 19 patients from a cohort of 278 consecutive patients. All patients were previously treated with radiotherapy (RT), whereas 13/19 (68%) previously received chemoradiotherapy. The median time from RT to TL was 10.98 years (range, 0.67–23.94 years). Aspiration was evident preoperatively in 17/19 (89%) patients, with 11 experiencing recurrent aspiration pneumonia. Seventeen of 19 (89%) patients were nil per os (NPO) requiring enteral nutrition. Six of 19 (32%) patients had surgical complications, including three (16%) pharyngocutaneous fistulas. At 3‐month and 1‐year postoperative follow‐up, there was significant improvement in mean Functional Oral Intake Scale (FOIS) score and aspiration, recurrent pneumonia, enteral nutrition, and NPO status rates ( P < .05). At 1‐year follow‐up, no patients were NPO, and only one patient required gastrostomy tube supplementation. Mean FOIS score increased from 1.3 to 6.1 ( P = .001). Eight of 13 patients (62%) were actively using a tracheoesophageal prosthesis at 1‐year follow‐up. Conclusions: Laryngectomy for dysfunctional larynx eliminates the morbidity of aspiration while improving diet and reducing gastrostomy tube dependence with an acceptable complication rate. Level of Evidence: 4. Laryngoscope, 128:597–602, 2018